A widow's tale : the 1884-1896 diary of Helen Mar Kimball Whitney - Whitney, Helen Mar, 1828-1896 (Life writings of frontier women, 2003)
Volume 6, Life Writings of Frontier Women series. Few diaries, journals, and memoirs published have provided as rich and well rounded a window into their authors' lives and worlds as the diary of Helen Mar Kimball Whitney. Because it provides a rare account of the widely experienced situations and problems faced by widows, her record has relevance far beyond Mormon history.